THE EFFECT OF PHOTOPERIOD ON THE GROWTH AND SURVIVAL OF AFRICAN MUDFISH Heterobranchus bidorsalis - UDE, E. F. (Nigerian Journal of Fisheries, 2012)
The effect of three photoperiods on growth and survival of African mudfish, Heterobranchus bidorsalis juveniles was investigated for a period of 56 days. Forty five juveniles of initial average weight of 35g were exposed to total darkness, partial darkness and full light throughout the study period in a partial flow-through system under laboratory conditions. The juveniles were stocked in triplicate treatment and fed 45% crude protein prepared diet daily at 5% body weight. Juveniles reared in total darkness exhibited significant (P<0.01) higher feed intake, weight gain, specific growth rate, protein efficiency ratio, and lowest percentage mortality than those cultured in partial darkness. Similarly, same parameters were significantly (P<0.01) higher in juveniles reared in partial light than those in full light. Also, the juveniles cultured in total darkness had significantly (P<0.01) lowest uneaten feed and feed conversion ratio, than those reared in partial darkness and full light. Fish cultured in total darkness had darker skin colorations than those in full light. It was concluded that rearing Heterobranchus bidorsalis in totally dark culture chamber could result in reduced wastage of feed, improved growth rate and enhanced profit especially in the developing countries where fish production presents strong potential in alleviating food crisis.